Endocrine phenotype of 6q16.1–q21 deletion involving SIM1 and Prader–Willi syndrome‐like features. Issue 12 (16th August 2013) - Izumi, Kosuke; Housam, Ryan; Kapadia, Chirag; Stallings, Virginia A.; Medne, Livija; Shaikh, Tamim H.; Kublaoui, Bassil M.; Zackai, Elaine H.; Grimberg, Adda
Abstract : Proximal interstitial 6q deletion involving Single‐minded 1 ( SIM1 ) gene causes a syndromic form of obesity mimicking Prader–Willi syndrome. In addition to obesity, Prader–Willi syndrome includes several other endocrinopathies, such as hypothyroidism, growth hormone deficiency, and hypogonadotropic hypogonadism. The endocrine phenotype of interstitial 6q deletion remains largely unknown, although clinical similarities between Prader–Willi syndrome and interstitial 6q deletion suggest endocrine abnormalities also may contribute to the interstitial 6q deletion phenotype. This report describes the endocrine phenotype in a propositus with the Prader–Willi‐like syndrome associated with an interstitial 6q deletion including the SIM1 gene. Detailed endocrine evaluation of the propositus during childhood and adolescence revealed hypopituitarism, though initial endocrine evaluations during infancy were unremarkable. Our patient raises the possibility that hypopituitarism may be part of the phenotype, especially short stature, caused by interstitial 6q deletion. SIM1 plays an important role in the development of neuroendocrine lineage cells, implicating SIM1 haploinsufficiency in the pathophysiology of hypopituitarism seen in our propositus. Early identification of endocrine abnormalities can improve clinical outcome by allowing timely introduction of hormone replacement therapy. Hence, we suggest that detailed endocrine evaluation and longitudinal endocrine follow up be performed in individuals with proximal interstitial 6q deletion involving SIM1 . © 2013 Wiley Periodicals, Inc.